Resources for Change: the Relationships of Organizational Inducements and Psychological Resilience to Employees' Attitudes and Behaviors toward Organizational Change - Shin, Jiseon; Taylor, M. Susan; Seo, Myeong-Gu (Academy of Management Journal, 2012)
We tested the importance of two hypothesized resources—organizational inducements and employee psychological resilience—in determining employees' commitment to, and supportive behaviors for, organizational change. Conducting a two-wave survey in a sample of 234 employees and 45 managers, we found that organizational inducements and resilience were positively related to two types of employees' commitment to change (normative and affective) and that these effects were mediated through state positive affect and social exchange. We also found that the two types of commitment to change were positively but differentially related to behavioral and creative support for change, and negatively related to turnover.